The Analysis of Microteaching In Improving Teaching Skill Of Pre-Service Physics Teachers (Journal of Innovative Science Education, 2019)
Microteaching is a method of teaching practice to provise pre-service teachers in mastering basic teaching skills. The aim of this study was to find out the effectiveness of microteaching learning in improving teaching skill of pre-service Physics teachers at Khairun Ternate University. The method of this study was a qualitative descriptive to analyse the effectiveness of microteaching learning towards teaching skill of pre-service physics teachers. The sample of this study was 20 students of 2016’class. The instrument used was a rubric sheet for assessing teaching skills. The result of the study showed that the implementation of microteaching, the skills of opening and closing lessons, questioning skills, explaining skills, strengthening skills, classroom management skills, and small group discussion skills also individual skills were very good and those are effective in improving teaching skill of pre-service Physics teachers